2019
DOI: 10.1109/tro.2018.2888977
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Agility For Multilegged Terrestrial Robots

Abstract: In this paper, we present a novel and practical approach for benchmarking agility. We focus on terrestrial, multi-legged locomotion in the field of bio-inspired robotics. We define agility as the ability to perform a set of different but specific tasks executed in a fast and efficient manner. This definition is inspired by the analysis of natural role models, such as dogs and horses as well as robotic systems. An evaluation of existing benchmarks in robotics is done and taken into account in our proposed bench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…Fungsi dari benchmark adalah pengujian terhadap perangkat keras pada central prosessing unit (CPU). Dimana komputer merupakan alat pengolah data yang sudah di tanamkan sebuah prosedur yang telah dirumuskan [9]. Komputer diciptakan dengan tujuan untuk melakukan perhitungan arimetika dan tanpa ada mesin pembantu [10].…”
Section: Pengujian Pada Perangkat Keras Yang Akan DI Bechmarkunclassified
“…Fungsi dari benchmark adalah pengujian terhadap perangkat keras pada central prosessing unit (CPU). Dimana komputer merupakan alat pengolah data yang sudah di tanamkan sebuah prosedur yang telah dirumuskan [9]. Komputer diciptakan dengan tujuan untuk melakukan perhitungan arimetika dan tanpa ada mesin pembantu [10].…”
Section: Pengujian Pada Perangkat Keras Yang Akan DI Bechmarkunclassified
“…In this short review, our focus on versatility shown by different quadrupedal robots is highlighted in the following paragraphs. Classifying existing robots by their versatility or agility in a benchmark like [1] is difficult, as only information from previous publications is available. Often included are however the absolute or relative speed, geometric measures and sometimes slope-inclinations, jump-heights or the robot's capabilities for turning.…”
Section: State-of-the-art: Versatile Legged Terrestrial Robotsmentioning
confidence: 99%
“…Two aspects that are especially striking in this context are versatility and agility. Presented originally in [1], agility is defined as follows: "Agility is representing a previously acquired and size dependent set of locomotion skills, executed in a precise, fast and ideally reflexive manner to an outside stimulus.". Comparing this definition to the one of versatility from the Oxford Dictionary (en.oxforddictionaries.com): "Ability to adapt or be adapted to many functions or activities" a new definition of agility as fast versatility or fast execution of rich motion skills may be called for.…”
Section: Introductionmentioning
confidence: 99%
“…The design of bionic robots has benefited from the introduction of robust and energy-saving movements based on those of animals. When compared with wheeled robots and other types of legged robots, quadruped robots can perform in response to external stimulation in an accurate and ideal manner of conditioned reflection and have the natural advantages of trafficability and agility on complex outdoor terrain [ 1 , 2 ]. At the same time, these robots offer further advantages in terms of dynamic locomotion, stability and manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%